Visual Rhetorical Analysis of Chinese International Communication Teaching on Instagram in The Digital Era: A Case Study of Silk Mandarin: 数字时代汉语国际传播在Instagram上教学的视觉修辞研究——以《丝合汉语》为列 - Tela, Irvan Aditya; Yu, Zhang; Waru, Dian Sari Unga (Published by Confucius Institute UNS, 2025)
Silk Mandarin (丝合汉语), as a Chinese language teaching organization, exemplifies the growing global interest in Mandarin. By leveraging platforms such as Instagram, Silk Mandarin actively promotes and disseminates Chinese language education internationally through visual media, including images and short videos. This research aims to investigate the role of visual rhetoric in the international dissemination of Mandarin and to analyze the types of content that are most effective in promoting Chinese language education. To achieve this, a comprehensive analysis of visual rhetoric is conducted, employing content analysis and literature review. The findings indicate that the global promotion of Mandarin is primarily facilitated through educational, cultural, and tourism-related content, predominantly conveyed through visually engaging media. Notably, linguistic messages, coded iconographic messages, and uncoded iconographic messages emerge as the primary vehicles for dissemination. Furthermore, Silk Mandarin adeptly utilizes these three forms of visual semiotic messages as integral components of its marketing strategy. This multifaceted approach not only ignites the audience's interest in learning Mandarin but also significantly influences their perceptions, encouraging them to appreciate the allure of China through the lens of an alternative image presented by the medium.